A Case of Fatal Malignant Hyperthermia During Pes Equinovarus Surgery in a Child - Ümüt Altuğ; Fulya Kamit Can; Ayşe Berna Anıl; Fatih Durak; Meltem Çakmak; Gökçen Özçifçi (Galenos Yayinevi, 2018)
Malignant hyperthermia (MH) is a genetic syndrome characterized by hyperthermia, tachycardia, acidosis, and muscle rigidity, often triggered by depolarizing muscle relaxants such as volatile anesthetics and/or succinylcholine. MH usually develops following anesthesia induction, but may occur during and after a surgical intervention. A 4.5-year-old boy was admitted to the pediatric intensive care unit considering MH due to persistent fever, tachycardia and end-tidal carbon dioxide elevation which developed during pes equinovarus surgery. In the follow-up, hypercapnia, fever and refractory metabolic acidosis recurred. Despite the administration of dantrolene sodium and supportive treatments, the patient died. This case is presented to remind the possibility of MH which may be fatal in patients receiving general anesthesia and to emphasize the follow-up and treatment of the patients with MH in pediatric intensive care unit.